Tradición y erudición en el libro XIII de Deipnosophistai de Ateneo de Naucratis - Sanchis Llopis, Jordi, 1957- (Minerva: Revista de filología clásica, 1994)
Athenaeus of Naucratis did not only transcribe skilfully and learnedly texts written by authors from previous days, but also had a wide knowledge of the literary tradition, which enabled him to create a structurally coherent work belonging to the symposiac genre. Within the work Deipnosophistai, book XIII is a good example of the grammarian's literary achievements. On women is not only a έρωτικός λόγος adapted to the literary demands of his time but also a real encyclopaedia of 'erotic' literature ranging from Homer to the Hellenistic period.